Pengukuran Tingkat Kepuasan Terhadap Website Booking Bromo Menggunakan Metode Webqual 4.0 Modifikasi - Muhammad Ridwan; Asif Faroqi; Anita Wulansari (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
This study aims to measure user satisfaction with the Booking Bromo website using the Modified WebQual 4.0 method. The website is used by tourists to book entrance tickets to Bromo Tengger Semeru National Park (TNBTS); however, there have been complaints about service quality, such as frequent server inaccessibility, a monotonous website design, and a lack of community interaction features. Using a quantitative approach, the study involved 338 respondents who were users of the Booking Bromo website. Data were collected through a questionnaire measuring variables such as Usability Quality, Information Quality, Service Interaction Quality, Visual Quality, and User Satisfaction. The results show that Usability Quality and Information Quality significantly influence User Satisfaction, while Service Interaction Quality requires improvement, particularly in transaction security and user communication features. This study provides recommendations to enhance website service quality and features to improve user satisfaction, such as improving server stability, providing clearer information, and adding more interactive community communication features.